2013
DOI: 10.2528/pierb13082207
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Breast Screening in the Time-Domain: Identification and Compensation of Measurement-Induced Uncertainties

Abstract: Abstract-In this work we examine several sources of measurement uncertainty that can hinder the use of time-domain microwave techniques for breast imaging. The effects that are investigated include those due to clock and trigger jitter, antenna movements, discrepancies in antenna fabrication, and random measurement noise. We explore the significance of the noise contribution of each effect, and present methods to mitigate them when possible and necessary. We demonstrate that, after applying the aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Prior to inputting the data into an imaging algorithm, each signal is filtered to remove content outside of the frequency range of the transmitted pulse using a low-pass filter with a cutoff at the upper limit of the frequency range of interest. Jitter is compensated for by time aligning the data using the correlation alignment method presented in [16]. The algorithm used is the Delay-Multiplyand-Sum (DMAS) method [17].…”
Section: Imaging Analysis and Resultsmentioning
confidence: 99%
“…Prior to inputting the data into an imaging algorithm, each signal is filtered to remove content outside of the frequency range of the transmitted pulse using a low-pass filter with a cutoff at the upper limit of the frequency range of interest. Jitter is compensated for by time aligning the data using the correlation alignment method presented in [16]. The algorithm used is the Delay-Multiplyand-Sum (DMAS) method [17].…”
Section: Imaging Analysis and Resultsmentioning
confidence: 99%
“…The physical factors that could affect measurement repeatability are also numerous. In [13] we saw that antenna movement within the radome can cause up to 11 mV of additional vertical noise (on the same order of magnitude as the signal for some transmit-receive antenna pairs). Thus, for test scenarios presented here, we never move the antennas.…”
Section: Sources Of Measurement Uncertainty and Errorsmentioning
confidence: 99%
“…Related to our system, in [12], we performed a study on homogeneous breast phantoms in which we identified sources of horizontal and vertical uncertainty, and saw how these uncertainties affected reconstructed breast images. Similarly, in [13] we analyzed how antennas affect the data and corresponding images generated from phantoms. In [14], we presented a small-scale study on four patients to observe the variation in scans performed on the same day.…”
Section: Introductionmentioning
confidence: 99%
“…By performing the data pre-processing, we remove the variability associated with measurement uncertainty. Here, we present a summary of the steps followed to mitigate these effects (a complete analysis can be found in [27]) and to prepare the data for the classification algorithms.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…These sources of jitter cause the misalignment of subsequent time-domain recordings; the signals recorded from various breast scans, will be out of phase with respect to each other. As in [27], we mitigate the effects of jitter by implementing a correlation alignment procedure; signals are shifted by some ∆T that maximizes the cross-correlation between the signals.…”
Section: Data Pre-processingmentioning
confidence: 99%